Precast concrete piles (Thomas Telford, 1986)
This technical report deals with the design, production and installation of both normal steel reinforced piles and prestressed piles.
Keywords: Concrete piling -- Design and construction.; Precast concrete construction.; elektronické knihy; electronic books